The Resilience of Poor Urban Families during the Covid-19 Pandemic (A Study in Kuranji District, Padang) - Melda Neli; Fatmariza Fatmariza (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2022)
The paper is attracted by the situation during the Covid-19 pandemic which has had an impact on the economy in Indonesia. The importance of the ability to be able to overcome, adapt and survive the poverty that befalls individuals in the midst of life in urban areas. Poor families who live in urban areas must be resilient to be able to live in cities that are densely populated and have minimal job opportunities. Therefore, this article wants to show how resilient poor families are during the Covid-19 pandemic. However, not a few of them have endurance or resilience. They have proven capable of facing challenges and able to deal with difficulties during the Covid-19 pandemic. This research aims to (1) analyze how resilient poor families are in facing the Covid-19 pandemic (2) analyze what the resilience values ​​of urban poor families are during the Covid-19 pandemic, (3) analyze the resilience efforts of urban poor families in during the Covid-19 pandemic. Using qualitative methods with case study research. The informants in this research were seven (7) informants for 4 (four) months, namely from December 2021 – March 2022), which was carried out by observation, interviews and documentation. Meanwhile, to analyze data using data reduction, data presentation and drawing conclusions. This research succeeded in showing that urban poor people during the Covid-19 era were able to survive by adapting to new situations, using savings, assistance from the government and looking for other jobs. The efforts they make to be able to rise during the pandemic are by not giving up easily, being grateful for the situation, accepting the situation, being optimistic and having self-efficacy/confidence. The Covid-19 pandemic period was able to foster values ​​including the value of independence, the value of hard work, the value of social care, the value of empathy and the value of reaching out.